Paraben Compounds—Part II: An Overview of Advanced Oxidation Processes for Their Degradation - Lincho, João (2021)
Water scarcity represents a problem for billions of people and is expected to get worse in the future. To guarantee people’s water needs, the use of “first-hand water” or the reuse of wastewater must be done. Wastewater treatment and reuse are favorable for this purpose, since first-hand water is scarce and the economic needs for the exploration of this type of water are increasing. In wastewater treatment, it is important to remove contaminants of emerging concern, as well as pathogenic agents. Parabens are used in daily products as preservatives and are detected in different water sources. These compounds are related to different human health problems due to their endocrine-disrupting behavior, as well as several problems in animals. Thus, their removal from water streams is essential to achieve safe reusable water. Advanced Oxidation Processes (AOPs) are considered very promising technologies for wastewater treatment and can be used as alternatives or as complements of the conventional wastewater treatments that are inefficient in the removal of such contaminants. Different AOP technologies such as ozonation, catalytic ozonation, photocatalytic ozonation, Fenton’s, and photocatalysis, among others, have already been used for parabens abatement. This manuscript critically overviews several AOP technologies used in parabens abatement. These treatments were evaluated in terms of ecotoxicological assessment since the resulting by-products of parabens abatement can be more toxic than the parent compounds. The economic aspect was also analyzed to evaluate and compare the considered technologies.